Conductive paste for solar cells capable of printing fine lines and widths and preparation method thereof

By using a combination of a variety of resins and organic solvents in the conductive paste of solar cell, the surface quality problem caused by the concentration of solvent volatility temperature during the sintering process is solved, and the thin line width and energy consumption are reduced.

CN116631671BActive Publication Date: 2025-04-08NANTONG AISHENG NEW ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310585380.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-23
Publication Date
2025-04-08
Estimated Expiration
2043-05-23

AI Technical Summary

Technical Problem

During the sintering process, the solvent volatilization temperature of existing solar cell conductive pastes is concentrated, resulting in poor surface quality and the presence of protrusions, hollows or microcracks, which affects printing performance. At the same time, the use of a single resin is difficult to ensure that the thin wire line width after printing and sintering is narrow, which increases energy consumption.

Method used

A conductive paste consisting of 2-5 parts of glass powder, 0.5-3 parts of aluminum powder, 75-90 parts of silver powder, and 5-20 parts of organic carrier is used, and the organic carrier includes at least a thermoplastic resin, a high adhesion resin, a dispersant, an organic solvent and a thixotropic agent. The viscosity of the conductive paste is reduced by combining the thermoplastic resin SEPS and the high adhesion resin rosin resin, and the volatility temperature of the solvent is optimized by combining the organic solvents of dodecanol ester, diethylene glycol butyl ether and dimethyl adipic acid.

Benefits of technology

The thin line width after printing and sintering is achieved by less than 25 microns, reducing the light-shielding area of ​​the electrode, reducing energy consumption, and ensuring the surface quality of the conductive paste, avoiding the occurrence of protrusions, holes or microcracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004243090160000081
    Figure BDA0004243090160000081
Patent Text Reader

Abstract

The present invention belongs to the technical field of solar cells, and in particular to the field of H01Q1 / 22, and more specifically to a conductive paste for solar cells capable of fine line width printing and a preparation method thereof, wherein the raw materials for preparing the conductive paste for solar cells include at least 2-5 parts of glass powder, 0.5-3 parts of aluminum powder, 75-90 parts of silver powder, and 5-20 parts of organic carriers by mass; the organic carrier includes at least a thermoplastic resin, a high adhesion resin, a dispersant, an organic solvent, and a thixotropic agent. The conductive paste for solar cells prepared by using raw materials of specific components can realize fine line width printing, realizes fine grid screen printing of 11-13 microns, and ensures that the fine line width after printing and sintering is less than 25 microns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, in particular to the field of H01Q1 / 22, and more specifically to a conductive paste for solar cells capable of printing fine lines and widths and a preparation method thereof. Background Art

[0002] At present, the most common solar cells on the market are mainly silicon-based solar cells, including crystalline silicon, polycrystalline silicon, and amorphous silicon thin-film cells. Among them, the front electrode, as an important component of the solar cell, mainly plays the role of collecting current, and at the same time has a decisive influence on the light-receiving area and series resistance of the battery. Therefore, the front electrode is one of the important factors affecting the conversion efficiency of solar cells. The conductive paste currently used in positive electrode materials is generally composed of silver powder, glass powder and organic carriers. The raw materials of the organic carrier mainly include organic solvents, polymer resins, thixotropic agents, leveling agents, surfactants, etc. It uses physical action to knead silver powder and inorganic adhesives together to form a conductive paste, and makes the conductive paste suitable for screen printing viscosity, thixotropy and other rheological properties, so that the application of screen printing technology can obtain the desired printing accuracy effect.

[0003] The selection principle of organic carrier is: the slurry must be in a relatively stable suspension, and can be placed for a long time without precipitation, and the printing performance can be guaranteed; during the sintering process, the organic carrier must be completely volatilized, the ash produced should be as little as possible, and the impact on the conductive performance is small. The conductive slurry is printed on the silicon substrate by screen printing. The technical requirements of the front silver paste used are good conductivity while obtaining the maximum light receiving area, and the electrical energy generated by the silicon wafer is output to the greatest extent. In summary, the screen printing accuracy and printability of the silver paste must be good, and it must be able to adapt to the increasingly narrow fine line screen printing, and the electrode width after printing and sintering should be as narrow as possible, thereby reducing the shading area of ​​the electrode, ensuring the reduction of the series resistance of the fine gate electrode, and improving the battery efficiency.

[0004] The prior art is that CN102903420B discloses a conductive paste and a preparation method thereof, wherein the raw materials for preparation include silver powder, glass powder, and an organic carrier, wherein the organic carrier includes an organic solvent, and the organic solvent can be one of alcohols or esters such as pine alcohol, butyl carbitol, and tributyl citrate. After printing and sintering on the surface of a solar cell, the conductive paste of the present invention can form a grid line with a smooth surface, thereby improving the battery efficiency of the solar cell; if the organic carrier in the paste includes only one solvent, the solvent volatilization temperature is concentrated and the volatilization rate is too fast during the sintering process, resulting in poor surface quality, protrusions, voids or microcracks, which seriously affect the performance of the printed paste. The prior art is that CN103093862B discloses a solar cell, wherein the raw materials for preparation include silver powder, aluminum powder, lead oxide powder, and an organic carrier, wherein the organic carrier includes an alcohol solvent, an ester solvent, ethyl cellulose, and an epoxy resin, but if the raw materials for preparation include only one resin, it is not conducive to the plasticity of the system, and it is difficult to ensure that the fine line width after printing and sintering is narrow, and it will also increase energy consumption. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present invention provides a conductive paste for solar cells that can be printed with fine lines and widths, and its preparation raw materials include at least 2-5 parts of glass powder; 0.5-3 parts of aluminum powder, 75-90 parts of silver powder, and 5-20 parts of organic carrier; the organic carrier includes at least thermoplastic resin, high adhesion resin, dispersant, organic solvent, and thixotropic agent.

[0006] Preferably, the organic carrier comprises at least the following by mass percentage: 5-10% thermoplastic resin, 1.5-7.5% high adhesion resin, 1-4.5% dispersant, 70-82% organic solvent, and 4-7% thixotropic agent.

[0007] Preferably, the thermoplastic resin includes at least one of SEBS, SEPS, SEEPS, ABS, acrylic resin, polyethylene glycol acrylate, polyvinyl alcohol, and polyvinyl alcohol copolymer.

[0008] Further preferably, the thermoplastic resin includes at least SEPS.

[0009] Preferably, the raw materials for preparing the glass powder include 3 to 10 parts of SiO2, 1 to 5 parts of Al2O3, 20 to 35 parts of B2O3, 5 to 20 parts of ZnO, and 30 to 70 parts of PbO in terms of mass fractions.

[0010] Preferably, the particle size of the aluminum powder is 800-1340 mesh.

[0011] Further preferably, the particle size of the aluminum powder may include 800, 1000, 1200 or 1340 mesh.

[0012] Preferably, the silver powder includes micron silver powder and nano silver powder, the particle size of the micron silver powder is 3-8 μm, and the particle size of the nano silver powder is 20-80 nm; the mass ratio of the micron silver powder to the nano silver powder is 1:(1-3).

[0013] Further preferably, the mass ratio of the high adhesion resin to the thermoplastic resin is 1:(2-2.5).

[0014] As an implementable case, the mass ratio of the high adhesion resin to the thermoplastic resin may include 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4 or 1:2.5.

[0015] Preferably, the high adhesion resin is a resin containing polar groups hydroxyl or carboxyl, including at least one of acrylate modified polyester resin, rosin resin, polyvinyl carbonate, and rosin modified phenolic resin.

[0016] Further preferably, the high adhesion resin at least includes rosin resin.

[0017] Rosin resin acid contains double chains and carboxyl active genes; SEPS is a linear triblock copolymer with polystyrene as the terminal segment and ethylene-propylene copolymer obtained by hydrogenation of polyisoprene as the middle elastic block, and does not contain polar groups. The inventors found that when rosin resin and SEPS are used as raw materials for preparing organic carriers at the same time, due to the poor compatibility between the two resins, by using resins with poor compatibility, the viscosity of the conductive paste is effectively reduced, the conductive paste can be promoted to be evenly dispersed, and the line width of the fine line after printing and sintering can be ensured to be less than 25 microns, the shading area of ​​the electrode is reduced, and the energy consumption is effectively reduced; and the specific resin compounding of this system achieves the effect of using a viscosity regulator. If a viscosity regulator is used additionally, the battery is prone to irreversible chemical reactions during the charging and discharging process, which will lead to a decrease in battery performance.

[0018] The dispersant includes dispersant A and dispersant B; the dispersant A includes at least one of acrylate copolymer, polyether polyol and modified polyether, and dodecanoic acid; the dispersant B includes at least one of oleic acid, polyhydroxystearic acid, polyglycerol-2 dipolyhydroxystearate, polyhydroxystearic acid, and palmitic acid.

[0019] The dispersant A at least includes a modified polyether, and the dispersant B at least includes oleic acid.

[0020] The modified polyether at least includes polyether-modified silicone, and the model may include BYK-310.

[0021] The thixotropic agent includes at least one of polyamide wax, hydrogenated castor oil and metal soap.

[0022] Further preferably, the thixotropic agent at least includes polyamide wax.

[0023] Preferably, the organic solvent includes at least one of dodecyl alcohol ester, diethylene glycol butyl ether, dimethyl adipate, and diethylene glycol butyl ether acetate.

[0024] Further preferably, the organic solvent includes dodecyl alcohol ester, diethylene glycol butyl ether, and dimethyl adipate.

[0025] Further preferably, the mass ratio of the dodecyl alcohol ester, diethylene glycol butyl ether, and dimethyl adipate is (0.1-0.5):(1.2-2):(2-5).

[0026] Further preferably, the mass ratio of the dodecyl alcohol ester, diethylene glycol butyl ether, and dimethyl adipate may include 0.3:1.675:2.345, 0.2:1.5:3.4, or 0.4:1.8:2.8.

[0027] Dodecanol ester is a film-forming aid with excellent film-forming performance, and is particularly suitable for various slurry systems synthesized with styrene and vinyl acetate as raw materials. It has good compatibility with resins, low usage, low film-forming temperature, good film leveling and color development, low freezing point, and good hydrolysis stability. Diethylene glycol butyl ether can be used in organic carriers to improve the anti-sedimentation effect of silver paste, enhance fluidity, and have better screen printing performance. Dimethyl adipate is a high-boiling point solvent and can be used as a plasticizer. The inventors have found that when the above three solvents are compounded in a certain mass ratio, they can not only have better solubility for organic and inorganic components in the preparation of raw materials, but also have excellent volatility. During the sintering process of the battery, since the volatilization temperature of the solvent is relatively dispersed, the organic carrier can be completely volatilized, the ash produced will be reduced, and the performance of the battery will basically not be affected. If a single-component organic solvent is used, the solvent volatilization temperature is concentrated and the volatilization rate is too fast during the sintering process of the slurry, resulting in poor surface quality, protrusions, voids or microcracks, which seriously affect the performance of the printing slurry.

[0028] The second aspect of the present invention provides a method for preparing a conductive paste for solar cells capable of printing fine lines and line widths, comprising at least the following steps:

[0029] S1: Mix and stir the thermoplastic elastomer resin, the adhesion resin, the dispersant A, the dispersant B, the solvent and the thixotropic agent to obtain an organic carrier;

[0030] S2: Evenly mix the prepared organic carrier with glass powder, aluminum powder and silver powder to obtain a conductive paste for solar cells.

[0031] Preferably, in the step S1, the stirring temperature is 40-60° C., the stirring time is 20-45 min, and the stirring speed is 400-600 rpm.

[0032] As an implementable example, the stirring temperature may be 50° C., the stirring time may be 30 min, and the stirring speed may be 500 rpm.

[0033] Beneficial Effects

[0034] (i) In the present invention, the conductive paste for solar cells prepared by using raw materials of specific components can realize fine line width printing, realize fine grid screen printing of 11-13 microns, and ensure that the fine line width after printing and sintering is less than 25 microns.

[0035] (ii) In the present invention, the thermoplastic resin SEPS and the high adhesion resin rosin resin are compounded and used. Since the compatibility of these two resins is poor, the viscosity of the conductive paste is effectively reduced, and the conductive paste can be promoted to be evenly dispersed, thereby promoting the effect of screen printing.

[0036] (III) In the present invention, three organic solvents, namely, dodecanol ester, diethylene glycol butyl ether and dimethyl adipate, are compounded in an organic carrier in a mass ratio of (0.1-0.5): (1.2-2): (2-5). During the sintering process of the battery, since the evaporation temperature of the solvent is relatively dispersed, the organic carrier can be completely volatilized, the ash content is correspondingly reduced, and the performance of the battery is basically not affected.

[0037] (IV) In the present invention, in the conductive paste provided by the present invention, glass powder is an inorganic adhesive, and the softening point of the glass powder is 500-600°C, which can wet and adhere to the substrate during sintering of the conductive paste, thereby improving the conductive performance of the conductive paste and avoiding overburning or insufficient melting and flow of the melt, insufficient adhesion, and slow sintering process during the sintering process.

[0038] (V) In the present invention, the raw materials used in the preparation are relatively environmentally friendly, do not contain o-phthalates and bromine compounds, and meet the ROSH environmental protection requirements. DETAILED DESCRIPTION

[0039] Example 1

[0040] The first aspect of the present embodiment provides a conductive paste for solar cells that can be printed with fine lines and widths, and the raw materials for its preparation are calculated by weight: 4 parts of glass powder, 1 part of aluminum powder, 85.4 parts of silver powder, and 9.6 parts of organic carriers, wherein the organic carrier includes 1.2 parts of thermoplastic resin, 0.5 parts of high adhesion resin, 0.7 parts of thixotropic agent, 0.5 parts of dispersant, and 6.7 parts of organic solvent.

[0041] The raw materials for preparing the glass powder are 5 parts of SiO2, 3 parts of Al2O3, 30 parts of B2O3, 15 parts of ZnO, and 50 parts of PbO in terms of mass fractions.

[0042] The particle size of the aluminum powder is 1000 meshes.

[0043] The silver powder includes micron silver powder and nano silver powder; the particle size of the micron silver powder is 3-8 μm, and the particle size of the nano silver powder is 50 nm; the mass ratio of the micron silver powder to the nano silver powder is 1:1.

[0044] The thermoplastic resin is SEPS.

[0045] The high adhesion resin is rosin resin.

[0046] The thixotropic agent is polyamide wax.

[0047] The dispersant comprises 0.3 parts of dispersant A and 0.2 parts of dispersant B; the dispersant A is a modified polyether, and the modified polyether is polyether-modified silicone; the dispersant B is oleic acid, CAS No.: 112-80-1.

[0048] The organic solvent includes 1.675 parts of dodecyl alcohol ester (CAS No.: 25265-77-4), 2.68 parts of diethylene glycol butyl ether (CAS No.: 112-34-5), and 2.345 parts of dimethyl adipate (CAS No.: 627-93-0).

[0049] The second aspect of this embodiment provides a method for preparing a conductive paste for solar cells capable of printing fine lines and widths, the preparation method comprising:

[0050] S1: Mix the thermoplastic elastomer resin, adhesion resin, dispersant, solvent and thixotropic agent at 50°C and 500 rpm for 30 minutes to obtain an organic carrier;

[0051] S2: Evenly mix the prepared organic carrier with glass powder, aluminum powder and silver powder to obtain a conductive paste for solar cells.

[0052] Example 2

[0053] In a first aspect, the present embodiment provides a conductive paste for solar cells that can be printed with fine lines and line widths. The raw materials for its preparation are, in parts by mass: 4 parts of glass powder, 0.8 parts of aluminum powder, 86 parts of silver powder, and 9.2 parts of an organic carrier, wherein the organic carrier includes 0.8 parts of a thermoplastic resin, 0.9 parts of a high adhesion resin, 0.7 parts of a thixotropic agent, 0.5 parts of a dispersant, and 6.7 parts of an organic solvent.

[0054] The raw materials for preparing the glass powder are 5 parts of SiO2, 3 parts of Al2O3, 30 parts of B2O3, 15 parts of ZnO, and 50 parts of PbO in terms of mass fractions.

[0055] The particle size of the aluminum powder is 1000 meshes.

[0056] The silver powder includes micron silver powder and nano silver powder. The particle size of the micron silver powder is 3-8 μm, and the particle size of the nano silver powder is 50 nm. The mass ratio of the micron silver powder to the nano silver powder is 1:1.

[0057] The thermoplastic resin is SEPS.

[0058] The high adhesion resin is rosin resin.

[0059] The thixotropic agent is polyamide wax.

[0060] The dispersant comprises 0.3 parts of dispersant A and 0.2 parts of dispersant B; the dispersant A is a modified polyether, and the modified polyether is polyether-modified silicone; the dispersant B is oleic acid, CAS No.: 112-80-1.

[0061] The organic solvent includes 1.675 parts of dodecyl alcohol ester (CAS No.: 25265-77-4), 2.68 parts of diethylene glycol butyl ether (CAS No.: 112-34-5), and 2.345 parts of dimethyl adipate (CAS No.: 627-93-0).

[0062] The second aspect of this embodiment provides a method for preparing a conductive paste for solar cells capable of printing fine lines and widths, the preparation method comprising:

[0063] S1: Mix the thermoplastic elastomer resin, adhesion resin, dispersant, solvent and thixotropic agent at 50°C and 500 rpm for 30 minutes to obtain an organic carrier;

[0064] S2: Evenly mix the prepared organic carrier with glass powder, aluminum powder and silver powder to obtain a conductive paste for solar cells.

[0065] Example 3

[0066] The first aspect of the present embodiment provides a conductive paste for solar cells that can be printed with fine lines and widths, and the raw materials for its preparation are calculated by weight: 4 parts of glass powder, 1 part of aluminum powder, 85.4 parts of silver powder, and 9.6 parts of organic carriers, wherein the organic carrier includes 1.2 parts of thermoplastic resin, 0.5 parts of high adhesion resin, 0.7 parts of thixotropic agent, 0.5 parts of dispersant, and 6.7 parts of organic solvent.

[0067] The raw materials for preparing the glass powder are 5 parts of SiO2, 3 parts of Al2O3, 30 parts of B2O3, 15 parts of ZnO, and 50 parts of PbO in terms of mass fractions.

[0068] The particle size of the aluminum powder is 1000 meshes.

[0069] The silver powder includes micron silver powder and nano silver powder. The particle size of the micron silver powder is 3-8 μm, and the particle size of the nano silver powder is 50 nm. The mass ratio of the micron silver powder to the nano silver powder is 1:1.

[0070] The thermoplastic resin is polyacrylate.

[0071] The high adhesion resin is rosin resin.

[0072] The thixotropic agent is polyamide wax.

[0073] The dispersant comprises 0.3 parts of dispersant A and 0.2 parts of dispersant B; the dispersant A is a modified polyether, and the modified polyether is polyether-modified silicone; the dispersant B is oleic acid, CAS No.: 112-80-1.

[0074] The organic solvent includes 1.675 parts of dodecyl alcohol ester (CAS No.: 25265-77-4), 2.68 parts of diethylene glycol butyl ether (CAS No.: 112-34-5), and 2.345 parts of dimethyl adipate (CAS No.: 627-93-0).

[0075] The second aspect of this embodiment provides a method for preparing a conductive paste for solar cells capable of printing fine lines and widths, the preparation method comprising:

[0076] S1: Mix the thermoplastic elastomer resin, adhesion resin, dispersant, solvent and thixotropic agent at 50°C and 500 rpm for 30 minutes to obtain an organic carrier;

[0077] S2: Evenly mix the prepared organic carrier with glass powder, aluminum powder and silver powder to obtain a conductive paste for solar cells.

[0078] Performance Evaluation

[0079] 1: Viscosity test

[0080] Test object: Conductive paste prepared in Examples 1-3

[0081] Test conditions: 25°C, American Brookfield DVNXHBCP cone and plate viscometer, CPA-51Z 52Z rotor, rotor speed 5 rpm, and the test results are recorded in Table 1

[0082] 2: Printing screen fine grid width / micron

[0083] Test object: Conductive paste prepared in Examples 1-3

[0084] Test conditions: 3D profiler, and the test results are recorded in Table 1

[0085] 3: Width of fine line after printing and sintering / micron

[0086] Test object: Conductive paste prepared in Examples 1-3

[0087] Test conditions: 3D profiler, and the test results are recorded in Table 1

[0088] 4: Fine line height after printing and sintering / micron

[0089] Test object: Conductive paste prepared in Examples 1-3

[0090] Test conditions: 3D profiler, and the test results are recorded in Table 1

[0091] 5: Aspect Ratio

[0092] The aspect ratio is the ratio of the height of the fine line after printing and sintering to the width of the fine line after printing and sintering, and the results are recorded in Table 1 Table 1

[0093]

Claims

1. A conductive paste for solar cells capable of printing fine lines, characterized in that: The raw materials for preparation include at least 2-5 parts of glass powder, 0.5-3 parts of aluminum powder, 75-90 parts of silver powder, and 5-20 parts of organic carrier in terms of weight percentage; The organic carrier comprises at least 5-10% of thermoplastic resin, 1.5-7.5% of high adhesion resin, 1-4.5% of dispersant, 70-82% of organic solvent, and 4-7% of thixotropic agent according to mass percentage; The thermoplastic resin is SEPS; The high adhesion resin is rosin resin; The mass ratio of the high adhesion resin to the thermoplastic resin is 1:(2-2.5); The silver powder includes micron silver powder and nano silver powder, the particle size of the micron silver powder is 3-8 μm, the particle size of the nano silver powder is 20-80 nm, and the mass ratio of the micron silver powder to the nano silver powder is 1: (1-3); The organic solvent is a compound of dodecyl alcohol ester, diethylene glycol butyl ether and dimethyl adipate; The mass ratio of the dodecyl alcohol ester, diethylene glycol butyl ether and dimethyl adipate is (0.1-0.5): (1.2-2): (2-5).

2. The conductive paste for solar cells capable of printing fine lines and line widths according to claim 1, characterized in that: The raw materials for preparing the glass powder include 3 to 10 parts of SiO2, 1 to 5 parts of Al2O3, 20 to 35 parts of B2O3, 5 to 20 parts of ZnO, and 30 to 70 parts of PbO in terms of mass fractions.

3. The conductive paste for solar cells capable of fine line width printing according to claim 2, characterized in that: The dispersant includes dispersant A, and dispersant A includes at least one of acrylate copolymer, polyether polyol, modified polyether, and dodecanoic acid.

4. The conductive paste for solar cells capable of fine line width printing according to claim 3, characterized in that: The dispersant also includes dispersant B, which includes at least one of oleic acid, polyglycerol-2 dipolyhydroxystearate, polyhydroxystearic acid, and palmitic acid.

5. A method for preparing a conductive paste for solar cells capable of fine line width printing according to claim 4, characterized in that: At least the following steps are included: S1: mixing and stirring the thermoplastic resin, high adhesion resin, dispersant A, dispersant B, organic solvent and thixotropic agent to obtain an organic carrier; S2: Evenly mix the prepared organic carrier with glass powder, aluminum powder and silver powder to obtain a conductive paste for solar cells.

6. The method for preparing a conductive paste for solar cells capable of printing fine lines and line widths according to claim 5, characterized in that: In the step S1, the stirring temperature is 40-60° C., the stirring time is 20-45 min, and the stirring speed is 400-600 rpm.

Citation Information

Patent Citations

  • A conductive paste and its preparation method

    CN102903420B

  • A silver conductive paste for solar cells

    CN103093862B

  • Electric conduction slurry and application of electric conduction slurry in N type silicon wafer solar cells

    CN104795127A

  • PERC single-crystal front conductive paste organic carrier, preparation method and application of PERC single-crystal front conductive paste organic carrier

    CN115985551A